Increasing resilience of material supply by decentral urban factories and secondary raw materials - Meyer, K.; Görgens, S.; Juraschek, M.; Herrmann, C. (Frontiers in Manufacturing Technology, 2023)
Current production processes are frequently dependent on global supply chains for raw materials and prefabricated inputs. With rising political and global risks, these supply networks are threatened, which leads to a reduction of supply chain resilience. At the same time, urban areas are currently one of the main consumers of products and waste material generators. The raw materials sourcing for this consumption commonly takes place in globally connected supply chains due to economy of scale effects. Therefore, cities are especially vulnerable to supply chain disruptions. A recent development which could reduce this vulnerability is the installation of urban factories among other urban production concepts, which can be symbiotically embedded into the urban metabolism to utilize the locally available (waste) materials. This, however, is hampered by the smaller production scale of decentralized urban production facilities, limited knowledge and challenges about the urban material flows and their characteristics. Against this background, we introduce a new factory type which is placed between the primary and secondary industrial sector: An urban secondary raw material factory which utilizes local waste material and other urban material flows for the extraction and refinement of secondary raw materials to supply production sites in its surrounding environment. To enable this small- to medium-scale factory type, the application of new production technologies plays a crucial role. Therefore, this paper proposes an approach for matching relevant potential waste streams to different technologies for waste-to-resource refinement. The applicability of the method for identification and evaluation of suitable technologies regarding their potential to be located in urban environments is demonstrated for plastic materials. Subsequently, key challenges and characteristics of the new factory type are summarized.